Pengaruh Job Insecurity, Kepuasan Kerja Dan Komitmen Organisasi Terhadap Turnover Intention di Madrasah Aliyah Negeri Karo - Anastasya Br Ginting; Annio Indah Lestari Nasution; Laylan Syafina (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This study aims to determine the effect of Job Insecurity, Job Satisfaction and Organizational Commitment on Turnover Intention at Madrasah Aliyah Negeri Karo. Madrasah Aliyah Negeri Karo is one of the Religious Education institutions in Karo Regency. The data analysis model used is multiple linear regression using SPSS software version 25. The coefficient of determination (R2) is obtained at 0.131 or 13% which explains that the independent variables job insecurity, job satisfaction and organizational commitment are able to explain their effect on the variable turnover intention of 13 %, while the remaining 87% is influenced by other factors outside of this study. The results of the research at the 95% level of confidence and a test of level 5% show that partially job insecurity has no effect on turnover intention, then job satisfaction has a negative and significant effect on turnover intention and organizational commitment has a positive and significant effect on turnover intention. Furthermore, simultaneously job insecurity, job satisfaction and organizational commitment have a positive and significant simultaneous effect on turnover intention at Madrasah Aliyah Negeri Karo.